The Methodical System of the Utsitization Process of "Computer Graphics" Science (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
From the injection of the subject "computer graphics", maksad told students that all kinds of graphic information(such as drawings, diagrams and schemes)performed from subjects of autonomy and specialization should be performed using graphic programs on a 2D scale or on a 3D triplet, as well as using practical, operational programs on a computer and a package of ready-made kidneys to.